A Case of Orbital Histoplasmosis. Issue 3 (May 2016) - Krakauer, Mark; Prendes, Mark Armando; Wilkes, Byron; Lee, Hui Bae Harold; Fraig, Mostafa; Nunery, William R.
Abstract : Histoplasma capsulatum var capsulatum is a dimorphic fungus endemic to the Ohio and Mississippi River Valleys of the United States. In this case report, a 33-year-old woman who presented with a right orbital mass causing progressive vision loss, diplopia, and facial swelling is described. Lateral orbitotomy with lateral orbital wall bone flap was performed for excisional biopsy of the lesion. The 1.5 × 1.8 × 2.3 cm cicatricial mass demonstrated a granulomatous lesion with necrosis and positive staining consistent with Histoplasma capsulatum var capsulatum infection. To the authors' knowledge, this is the first case of orbital histoplasmosis to be reported in the United States and the first case worldwide of orbital histoplasmosis due to Histoplasma capsulatum var capsulatum . Abstract : We describe the case of a patient in the United States with diplopia and decreased visual acuity secondary to a large orbital mass, diagnosed as a granulomatous lesion from infection with Histoplasma Capsulatum var Capsulatum.